ORGANIZING ACTIVE GAMES RELATED TO HANDBALL SPORT - Mo‘ydinov Iqboljon Abduxamidovich (The Conference Hub, 2025)
This study thoroughly investigates the process of organizing and conducting active games based on the sport of handball. Incorporating national active games into physical education lessons not only contributes to students' physical development but also enhances their mental and social skills. Through these games, students have the opportunity to collaborate, compete, and foster team spirit.
Keywords: physical education, handball, active games, national movements, team spirit, strategic thinking, educational process.